Applying GPR-FGRA hybrid algorithm for prediction and optimization of eco-friendly magnetorheological finishing Ti–6Al–4V alloy - Tien, Dung Hoang; Duy, Trinh Nguyen; Thoa, Pham Thi Thieu (International journal on interactive design and manufacturing, 2023)
To produce the mirror finish of the Ti–6Al–4V alloy workpieces, a newly developed polishing tool based on magnetic field assistance. This work has developed an environmentally friendly model of magnetic finishing with a carrier fluid natural origin combined with carbonyl and abrasive iron particles; and a new GPR-FGRA hybrid algorithm to predict, optimize and identify critical factors affecting material removal rate and surface quality. The best surface quality with the optimization method increased by 37.5% (Ra = 0.025 μm) when choosing the optimized cutting parameter with the GPR-FGRA hybrid algorithm compared with the Taguchi experimental analysis (Ra = 0.040 μm). The analysis results by the GPR-FGRA algorithm show that the prediction surface quality accuracy was more significant than 99.63%, and the working distances (K) had the most remarkable influence on the polishing effect, while the result of workpiece speed was the least important. This study provides excellent reference values for predicting, optimizing and identifying the main factors affecting surface quality and material removal rate in a polishing model for complex, expensive materials from low-cost and environmentally friendly materials.